2008
DOI: 10.1002/dmrr.815
|View full text |Cite
|
Sign up to set email alerts
|

Mild gestational hyperglycaemia as a risk factor for metabolic syndrome in pregnancy and adverse perinatal outcomes

Abstract: The prevalence of MS increases with the worsening of glucose tolerance and is an independent predictor of adverse perinatal outcomes; impaired glycaemic profile identifies pregnancies with important metabolic abnormalities that are linked to the occurrence of adverse perinatal outcomes even in the presence of a normal OGTT, in patients that are not currently classified as having GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 36 publications
(26 reference statements)
4
39
1
1
Order By: Relevance
“…Hence, in this study, the authors did not have a control group of untreated pregnant women with 2-h PG ≥ 7.8 mmol/L, as there are evidences confirming that the treatment of GDM women as defined by WHO criterion was associated with a reduced risk of pregnancy outcome (Crowther et al, 2005;Gayle et al, 2010). The policy of not treating women with 2-h PG ≥ 7.8 mmol/L amounts to deliberately exposing the pregnant mothers to unphysiological glycemic level despite our extensive knowledge of the benefits of treatment of mild hyperglycemia during pregnancy (Seshiah et al, 2008a;Landon et al, 2009;Bevier et al, 1999;Negrato et al, 2008). Wahi et al observed in their prospective study, the advantage of adhering to a cut-off level of 2-h PG ≥ 7.8 mmol/L in diagnosis and management of GDM for a significantly positive effect on pregnancy outcomes (Wahi et al, 2011).…”
Section: The Validation Of Who Criterion (Dipsi Criterion) Based On Tmentioning
confidence: 99%
“…Hence, in this study, the authors did not have a control group of untreated pregnant women with 2-h PG ≥ 7.8 mmol/L, as there are evidences confirming that the treatment of GDM women as defined by WHO criterion was associated with a reduced risk of pregnancy outcome (Crowther et al, 2005;Gayle et al, 2010). The policy of not treating women with 2-h PG ≥ 7.8 mmol/L amounts to deliberately exposing the pregnant mothers to unphysiological glycemic level despite our extensive knowledge of the benefits of treatment of mild hyperglycemia during pregnancy (Seshiah et al, 2008a;Landon et al, 2009;Bevier et al, 1999;Negrato et al, 2008). Wahi et al observed in their prospective study, the advantage of adhering to a cut-off level of 2-h PG ≥ 7.8 mmol/L in diagnosis and management of GDM for a significantly positive effect on pregnancy outcomes (Wahi et al, 2011).…”
Section: The Validation Of Who Criterion (Dipsi Criterion) Based On Tmentioning
confidence: 99%
“…A prospective observational quantitative study was conducted in the Perinatal Diabetes Center in the city of Botucatu, Southeastern Brazil, between 2007 and2008. Direct and indirect costs and disease-specifi c costs (medications and tests) were estimated.…”
Section: Methodsmentioning
confidence: 99%
“…The cutoffs used were those proposed by Carpenter & Coustan 3 for GTT, and Gilmer et al 8 for blood glucose profi le. Patients with abnormal GTT plus normal GP were diagnosed with gestational diabetes while those with normal GTT plus abnormal GP were diagnosed with mild hyperglycemia 15 and treated with diet alone as outpatients. Women with abnormal GTT plus abnormal GP, as well as those with pregestational diabetes were hospitalized for one day (24 hours) on a fortnight basis until 28 weeks of gestation, and on a weekly basis from week 28 until delivery, and were treated with diet plus insulin therapy for blood glucose control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…with a normal 100-g glucose tolerance test (GTT) but an abnormal glycemic profile, have perinatal outcomes comparable to those of diabetic women and should, therefore, receive comparable treatment. 5,6 The principal factor responsible for this is the need for strict glycemic control to maintain blood glucose levels within the normal range throughout pregnancy. 7 To obtain such control, these women are treated with diet and/or insulin therapy, and followed up on an outpatient basis or subjected to frequent short hospitalizations.…”
Section: Introductionmentioning
confidence: 99%